2009
DOI: 10.1111/j.1365-2966.2009.15623.x
|View full text |Cite
|
Sign up to set email alerts
|

Sweet–Parker current slab in a partially ionized plasma

Abstract: The formation of the Sweet-Parker current sheet, in fact a slab, is studied for a partially ionized plasma. The effects arising from the ion-neutral drag, the ambipolar diffusion, the resistivity resulting from electron-neutral and electron-ion collisions, and the Hall electric field are important for determining the dimensions of the current slab as well as the magnetic reconnection rate. It is the Hall effect that transforms the sheet into a slab. Along with the slab configuration, the out-of-plane plasma fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The role of ambipolar diffusion has been studied analytically in the context of magnetic reconnection. It has been found that in a Sweet-Parker geometry, the ambipolar diffusion increases the reconnection rate (Vishniac & Lazarian 1999;Krishan 2009). Some of the observations of magnetic field in the solar chromosphere suggest that reconnection can occur at speeds ∼ 0.1 VA (Dere 1996).…”
Section: Magnetic Reconnection In Partially Ionized Plasmamentioning
confidence: 99%
“…The role of ambipolar diffusion has been studied analytically in the context of magnetic reconnection. It has been found that in a Sweet-Parker geometry, the ambipolar diffusion increases the reconnection rate (Vishniac & Lazarian 1999;Krishan 2009). Some of the observations of magnetic field in the solar chromosphere suggest that reconnection can occur at speeds ∼ 0.1 VA (Dere 1996).…”
Section: Magnetic Reconnection In Partially Ionized Plasmamentioning
confidence: 99%